2014
DOI: 10.4103/0972-6748.144956
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variants of ADH, ALDH and the five factor model of personality in alcohol dependence syndrome

Abstract: Background:The etiology of alcohol dependence is a complex interplay of biopsychosocial factors. The genes for alcohol-metabolizing enzymes: Alcohol dehydrogenase (ADH2 and ADH3) and aldehyde dehydrogenase (ALDH2) exhibit functional polymorphisms. Vulnerability of alcohol dependence may also be in part due to heritable personality traits.Aim:To determine whether any association exists between polymorphisms of ADH2, ADH3 and ALDH2 and alcohol dependence syndrome in a group of Asian Indians. In addition, the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
9
2
Order By: Relevance
“…These results were not significant however, as they were for Malouff et al in tobacco smokers (Malouff et al 2007) and for Salujha in alcohol dependent participants (Salujha et al 2014) as well as Vollrath and Torgersen in alcohol consumers (Vollrath and Torgersen 2008). As these are cross-sectional studies, the results suggest that Neuroticism plays an important role in maintaining substance use but not necessarily in developing it.…”
Section: Discussionmentioning
confidence: 38%
See 4 more Smart Citations
“…These results were not significant however, as they were for Malouff et al in tobacco smokers (Malouff et al 2007) and for Salujha in alcohol dependent participants (Salujha et al 2014) as well as Vollrath and Torgersen in alcohol consumers (Vollrath and Torgersen 2008). As these are cross-sectional studies, the results suggest that Neuroticism plays an important role in maintaining substance use but not necessarily in developing it.…”
Section: Discussionmentioning
confidence: 38%
“…Synopsis studies suggest that substance use is mainly found in participants with a high score of Neuroticism, Extraversion, Openness and low score of Agreeableness and Conscientiousness (Clark et al 2012;Fridberg et al 2011;Malouff et al 2007;McCann 2010;Salujha et al 2014;Vollrath and Torgersen 2008;Waga and Iwahashi 2007): Concerning tobacco consumption Waga and Iwahashi found significantly high scores of Openness in Japanese students who smoke (Waga and Iwahashi 2007). In their meta-analysis Malouff et al revealed an association between alcohol consumption and high score of Neuroticism as well as low scores of Agreeableness and Conscientiousness (Malouff et al 2007).…”
Section: Contributersmentioning
confidence: 99%
See 3 more Smart Citations